The Role of Brief Note and Financial Literacy in Family Financial Management - Kasmiah; Risman; Masri Damang (Yayasan Amerta Insan Unggul, 2024)
This study explores the role of brief note-taking and financial literacy in improving family financial management, particularly among women as the primary household financial managers. Conducted in Lamokato Village, Kolaka Regency, Indonesia, the research employs a quantitative pretest–posttest design involving 53 households to evaluate changes in financial knowledge following an educational intervention. The study aims to strengthen financial awareness, planning, and decision-making as foundations of household economic resilience. The pretest results show that 62.3% of respondents had only moderate financial knowledge, while posttest data indicate a significant improvement, with 94.34% demonstrating good financial literacy. The findings reveal that the integration of brief note-taking—such as systematic recording of income and expenditures—combined with financial literacy education enhances the ability of families to manage resources, save, reduce debt, and initiate investments. Financial mismanagement and consumptive spending patterns are identified as primary barriers to family financial well-being. The study concludes that structured financial education programs effectively empower families, particularly women, to achieve better budgeting discipline and financial independence. These results highlight the essential role of financial literacy in reducing financial stress, promoting sustainable financial behavior, and supporting inclusive economic development. The study provides practical implications for policymakers and educators to design targeted community-based financial training programs that foster long-term household stability.